Variações rítmicas vivas na atuação cênica - Vinícius Assunção Albricker (2019)
The creative work with the rhythm in scenic acting was the trigger of the writing process of this thesis. We claim that the development of rhythmic variations in scenic acting is of major importance, provided that such variations are alive. In this sense, we focus on the actor’s creative composition, exploring fundamental properties of the concept of life that may contribute to his/her artistic formation and professional development. Considering the small number of publications written in Brazilian Portuguese about the actor’s creative work, the review and proposition of principles and procedures herein promoted are considered to be relevant contributions to the investigation of such theme. Therefore, we aimed at outlining the definitions of living scenic acting and living rhythmic variations concomitantly proposing principles and procedures to the actor’s work. To achieve this, we had to study important theatre authors, such as the British director Declan Donnellan and his concept of target; the Russian master Konstantin Stanislavsky and some of his disciples, considering his inestimable discoveries about organicity in acting; also, we reviewed some novel proposals by artists like Jerzy Grotovisky and Peter Brook regarding the search for an acting that is alive. Moreover, we explored references borrowed from music and fields of knowledge, such as biology and physics, in order to address a dialogue between art and science and, consequently, provide support to the conceptualization of what we call living rhythmic variations and living scenic acting. By connecting the information gathered and interpreted with our own pedagogical and artistic experiences, we outline a set of ideas, strategies and pedagogical practices, directed to the actor and his/her rhythms, highlighting attitudes that may stimulate the creation of a living scene. As a result, we reveal our particular perspective on how the interlacing among rhythm, life and acting occurs, and also offer conceptual and methodological proposals that can effectively contribute to the composition of living rhythmic variations in the art of scenic acting.